2019
DOI: 10.1097/pcc.0000000000002017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Levosimendan Versus Milrinone on the Occurrence Rate of Acute Kidney Injury Following Congenital Heart Surgery in Infants: A Randomized Clinical Trial*

Abstract: Objectives: It has been shown that, in contrast to other inotropic agents, levosimendan improves glomerular filtration rate after adult cardiac surgery. The aim of this study was to investigate the efficacy of levosimendan, compared with milrinone, in preventing acute kidney dysfunction in infants after open-heart surgery with cardiopulmonary bypass. Design: Two-center, double-blinded, prospective, randomized clinical trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Five studies focused on safety and side effects (Table 3). 11,[19][20][21]25,38,47 Collectively, selected studies reported on 12 medications in 2856 children: 15 studies focused on neonates or infants, and included 969 patients; 12 studies specified a surgical repair or congenital heart defect as part of the study population, including 5 studies that included only Norwood patients. All medications were given between the end of a bypass through the first 72 hours postoperatively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies focused on safety and side effects (Table 3). 11,[19][20][21]25,38,47 Collectively, selected studies reported on 12 medications in 2856 children: 15 studies focused on neonates or infants, and included 969 patients; 12 studies specified a surgical repair or congenital heart defect as part of the study population, including 5 studies that included only Norwood patients. All medications were given between the end of a bypass through the first 72 hours postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…Levosimendan is a calcium sensitiser, binding to the cardiac troponin C protein and preventing binding of troponin I for sustained cardiac myocyte contraction. [64][65][66] We examined 13 studies on 867 patients focused on the administration of levosimendan 10,16,[28][29][30][32][33][34][36][37][38] : 7 studies were retrospective, and 6 were prospective randomised controlled trials. The dosing range was 0.05-0.2 μg/kg/minute for 48-72 hours with or without a loading dose of 12-15 μg/kg.…”
Section: Vasopressinmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Thorlacius et al was a secondary analysis of the authors' previously published study evaluating effect of milrinone versus levosimendan on the occurrence rate of acute kidney injury after congenital heart surgery. 6 The initial study design was a randomized, prospective, double-blinded clinical drug trial based at 2 pediatric tertiary university hospitals. A total of 72 patients were enrolled, with ages ranging between 1 and 12 months.…”
mentioning
confidence: 99%